2013
DOI: 10.7314/apjcp.2013.14.11.6327
|View full text |Cite
|
Sign up to set email alerts
|

Stratifying Patients with Haematuria into High or Low Risk Groups for Bladder Cancer: a Novel Clinical Scoring System

Abstract: Haematuria is a common presentation of bladder cancer and requires a full urologic evaluation. This study aimed to develop a scoring system capable of stratifying patients with haematuria into high or low risk groups for having bladder cancer to help clinicians decide which patients need more urgent assessment. This crosssectional study included all adult patients referred for haematuria and subsequently undergoing full urological evaluation in the years 2001 to 2011. Risk factors with strong association with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Tan's scoring system demonstrated adequate discrimination in the first study (area under the ROC curve=80.4%) (Tan et al, 2013). Nevertheless, this model needs to be validated in a secondary dataset.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…Tan's scoring system demonstrated adequate discrimination in the first study (area under the ROC curve=80.4%) (Tan et al, 2013). Nevertheless, this model needs to be validated in a secondary dataset.…”
Section: Discussionmentioning
confidence: 94%
“…In addition, we observed a score of 12 as the best score threshold in our validation cohort. Tan et al (2013) reported that a threshold figure of 10 gives the scoring system a sensitivity of 90% and a specificity of 55.7%. Using the suggested cut-off value of 10 in our cohort, the scoring system had a sensitivity of 86.1% but a specificity of only 36.7%, while the cut-off value of 12 yielded a sensitivity of 69.6% and a specificity of 69.7%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several clinical prognostic characteristics, including age, gender, smoking history and degree of hematuria, are well-established as risk factors for UC in patients with hematuria [ 3 , 20 - 22 ]. Recently, several groups have attempted to develop models based on clinical prognostic characteristics to predict the risk of UC in patients with hematuria [ 20 - 22 ], but critically, these models offer limited accuracy and have largely focused on detecting patients with UC rather than ruling out patients who do not have disease. These detection-focused models have therefore been insufficient to reliably identify patients with disease during a primary evaluation, even if used in combination with urine cytology [ 20 - 22 ].…”
Section: Introductionmentioning
confidence: 99%